Faint Objects and How to Observe Them - Cudnik, Brian; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Astronomers' Observing Guides provide up-to-date information for amateur astronomers who want to know all about what it is they are observing. This is the basis of the first part of the book. The second part details observing techniques for practical astronomers, working with a range of different instruments. Faint Objects and How to Observe Them is for visual observers who want to "go deep" with their observing. It's a guide to some of the most distant, dim, and rarely observed objects in the sky, with background information on surveys and object lists -- some familiar and some not. Typically, amateur astronomers begin by looking at the brighter objects, and work their way "deeper" as their experience and skills improve. Faint Objects is about the faintest objects we can see with an amateur's telescope -- their physical nature, why they appear so dim, and how to track them down. By definition, these objects are hard to see! But moderate equipment (a decent telescope of at least 10-inch aperture) and the right techniques can reveal a surprising number of 'almost invisible' objects. The book provides basic tips on the type of telescope to use, how to record observations, and where to find lists and those all important finder charts. Here is a "one-stop shop" for those who are interested in taking their observational pursuits to the next level, and who want to see the most distant parts of the universe accessible to backyard telescopes.
Preface -- Pushing the Envelope in Visual Astronomical Observations -- Part I: The Physical Nature of Faint Objects -- Chapter 1: The Astronomical Surveys -- Chapter 2: The Astronomers Behind the Historical Surveys -- Chapter 3: The Nature of Star Clusters and Nebulae -- Chapter 4: The Nature of Galaxies and Galaxy Clusters -- Chapter 5: The Nature of Quasars and Other Exotics -- Chapter 6: Ground-and Space-Based Observations of the Most Distant Parts of the Universe -- Part II: How to Observe Faint Objects -- Chapter 7: General Guidelines for Observing Faint Objects -- Chapter 8: Preparation and the Observing Session -- Chapter 9: Some Suggested Observing Projects -- Chapter 10: Suggested Projects by Survey and Source -- Chapter 11: Recording Your Observations and Other Tips to Help You Stick with the Program -- Chapter 12: Citizen Science Activities and Searching for Supernovae -- A Few Final Thoughts -- Appendix A: References and Footnotes -- Appendix B: Glossary -- Appendix C: Resources Useful for the Observation of Faint Objects -- Appendix D: Observing Software -- Appendix E: Astronomical League Observing Clubs -- Appendix F: How to Find More Observing Lists of Faint Objects -- Index.
Keywords: Physics; Astronomy; Physics; Astronomy, Observations and Techniques; Popular Science in Astronomy